Kajian Kesiapan Masjid Agung Cianjur sebagai Pusat Kawasan Wisata Religi Kabupaten Cianjur - Sulfia M Andi; Bambang Pranggono (UNISBA Press, 2021)
Abstract. The Problems studied in this thesis are : to describe the Readiness of the Great Mosque of Cianjur as the Center for Religious Tourism Areas. The formulation of the problem studied in this thesis is: how is the readiness of the Great Mosque of cianjur as a religious tourism center. In this study, research methods, namely by describing the conditions that occurred in the field (field research). Data collection through observation, interviews (interviews), and documentation. The result of the study show that the level of readiness of religious tourism in the great mosque of cianjur area has been declared good but there is still a need for development in various aspects in order to maximize the readiness for the application of religious tourism. Abstrak. Persoalan yang dikaji dalam skripsi ini yaitu: untuk mendeskripsikan Kesiapan Masjid Agung Cianjur sebagai Pusat Kawasan Wisata Religi. Adapun rumusan masalah yang dikaji pada skripsi ini yaitu: bagaimana Kesiapan Masjid Agung Cianjur sebagai pusat wisata Religi. Dalam penelitian ini peneliti menggunakan metode penelitian deskriptif kualitatif, yakni dengan menggambarkan keadaan yang terjadi di lapangan (field research). pengumpulan data melalui observasi, wawancara (interview), dan dokumentasi. Hasil dari penelitian menunjukan tingkatkesiapan pariwisata Religi di Kawasan Masjid Agung Cianjur sudah dinyatakan baik namun masih perlu adanya pengembangan di berbagai aspek agar dapat memaksimalkan kesiapan penerapan pariwisata Religi.